Pola Komunikasi Interpersonal Ayah dan Anak dalam Membentuk Kepercayaan Diri Anak di Kota Tegal - Zaskia Nur Septiani; Diryo Suparto; Sarwo Edy (PERSPEKTIF, 2026)
This study aims to analyze communication patterns between fathers and children in shaping children’s self-confidence in Tegal City. This research employed a qualitative approach with a descriptive design. The informants were selected using purposive sampling and consisted of eight father–child pairs. Data were collected through in-depth interviews, observation, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The findings show that interpersonal communication between fathers and children plays an important role in developing children’s self-confidence. Open and empathetic communication makes children feel safe, heard, and valued. Fathers’ support and positive attitudes encourage children to try new experiences, participate in social activities, and develop positive self-perception. Meanwhile, equality in communication creates warm and pressure-free relationships, allowing children to express their opinions more confidently. Conversely, the lack of father involvement may create emotional distance and communication barriers that lead to functional fatherlessness. This study confirms that children’s self-confidence is shaped not only by internal factors but also by the quality of father-child communication that is emotionally present, consistent, and meaningful.